Analisis Hukum Ekonomi Syariah Terhadap Pembayaran Zakat Mengunakan Cryptocurrency - Hasanudin, Ade; Bahren, Rina Susanti Abidin; Nuroni, Abdul Muiz (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2025)
Zakat payment using cryptocurrency is an increasingly relevant topic along with the development of digital technology. In the context of sharia economic law, zakat is an obligation that must be fulfilled by every qualified Muslim, including cryptocurrency owners. This article analyzes how cryptocurrency is positioned as an asset that meets the criteria for assets that must be zakatable in Islamic law, as well as the legal and social implications of cryptocurrency-based zakat payments. By utilizing the blockchain technology that underlies cryptocurrency, zakat payments can be made more efficiently, transparently, and quickly, allowing for a fairer and more equitable distribution to mustahiq. Despite challenges related to regulation and legal understanding, this article concludes that cryptocurrency zakat has great potential in strengthening the Muslim economy, as long as it is supported by the right policies and education for the community.